2018
DOI: 10.3390/ma11112093
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Asphalt Rubber with Nanoclay towards Enhanced Storage Stability

Abstract: Asphalt rubber (AR), which is prepared by blending crumb rubber and bitumen, provides various advantages, including superior rutting resistance, lower road-tire noise and longer service life. However, contractors have expressed concerns regarding its poor storage stability, which in turn limits its wider application. This study aims to address the storage stability concern by incorporating nano-montmorillonite (nanoclay). Three types of nanoclay were dispersed into hot AR binder by high shear blending. The rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 29 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Table 5 presents the average values of LAS parameters (A and B) obtained from the VECD analysis. The A parameter is correlated with the fatigue life of the material while the parameter B indicates the material sensitivity to an applied shear strain [ 50 , 51 , 52 , 53 , 54 , 55 ]. When the values of LAS parameters of binders A and B are compared for the same aging state, it was observed that binder A presented a higher absolute value of the parameters, which indicates its superior fatigue performance.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 presents the average values of LAS parameters (A and B) obtained from the VECD analysis. The A parameter is correlated with the fatigue life of the material while the parameter B indicates the material sensitivity to an applied shear strain [ 50 , 51 , 52 , 53 , 54 , 55 ]. When the values of LAS parameters of binders A and B are compared for the same aging state, it was observed that binder A presented a higher absolute value of the parameters, which indicates its superior fatigue performance.…”
Section: Resultsmentioning
confidence: 99%
“…The colloidal size with adequate surface area can make the solid particles (nano-montmorillonite) move randomly in asphalt fractions rather than directly ascend (or descend) in vertical direction [35]. What's more, the stable disperse of nano-montmorillonites in virgin asphalt can also be attributed to the penetration of the asphalt fractions into the nano-montmorillonite layers, which modified the original structure to intercalated or exfoliated structure within asphalt components [17,21].…”
Section: Fatigue Performancementioning
confidence: 99%
“…This indicates that the enhanced rheological properties may ascribe to the interaction behavior of the polymer chains in asphalt binder into the interlayer of clay. Yu et al, [21] enhanced the storage stability of asphalt rubber by incorporating three types of nanoclays and improved the rheological properties through modification. Leng et al, [22] found that clay/SBS modified bitumen composites have acceptable storage performance.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-modified asphalt binders, such as SBS-modified binder, tire-rubber modified binder, aging modified binder, and so on, are more complex in comparison with the neat binder, also the blending degree is more variable than the pure asphalt binder. Since the viscosity of SBS-modified binder is higher than base bitumen, if SBS-modified binder is utilized in this experimental program, the blending degree of virgin and RAP binders will decrease, the viscosity of bitumen has a significant effect on the blending degree [40][41][42][43]. Additional research will be conducted to explore the influences of different bitumen contents and mixing parameters on the blending degree of virgin and RAP binders in RAM, thereby increasing the proportion of RAP in RAM.…”
Section: (A)mentioning
confidence: 99%